Surface Treatment on Nickel Oxide to Enhance the Efficiency of Inverted Perovskite Solar Cells - Kaijie Wang; Ye Tian; Heng Jiang; Meng Chen; Shuangyan Xu (International Journal of Photoenergy)
The organic-inorganic hybrid perovskites such as CH3NH3PbI3 have been considered as one of the most promising candidates for the next-generation photovoltaic materials due to its high absorption coefficient, low exciton binding energy, and long diffusion length. Herein, we have chosen NiOx as the hole transport material because metal oxides exhibit robust properties in air. We synthesized the NiOx film by a common sol-gel method. It is found that high-temperature annealing (500°C) is required to ensure the perovskite solar cell (PSC) with an efficiency over 15%. Low-temperature annealing (100°C) cannot convert the precursor materials to fully covered NiOx film, while the PSC based on mediate-temperature annealing (300°C) NiOx has larger resistance and thus lower efficiency. Fortunately, we have found that UV-ozone treatment on the NiOx film can reduce the resistance of the device based on 300°C annealed NiOx. The champion device can reach 16% efficiency with UV-ozone-treated 300°C annealed NiOx. This work has made it possible to reduce the annealing temperature of the sol-gel NiOx for high-efficiency PSCs, and it is believed that this simple surface treatment can be further employed in other metal oxide-based optoelectronic devices.